Netrin‐1 is required for efficient neural tube closure. Issue 2 (27th September 2012) - Kee, Nigel; Wilson, Nicole; Key, Brian; Cooper, Helen M.
Abstract During neural tube formation, neural plate cells migrate from the lateral aspects of the dorsal surface towards the midline. Elevation of the lateral regions of the neural plate produces the neural folds which then migrate to the midline where they fuse at their dorsal tips, generating a closed neural tube comprising an apicobasally polarized neuroepithelium. Our previous study identified a novel role for the axon guidance receptor neogenin in Xenopus neural tube formation. We demonstrated that loss of neogenin impeded neural fold apposition and neural tube closure. This study also revealed that neogenin, via its interaction with its ligand, RGMa, promoted cell–cell adhesion between neural plate cells as the neural folds elevated and between neuroepithelial cells within the neural tube. The second neogenin ligand, netrin‐1, has been implicated in cell migration and epithelial morphogenesis. Therefore, we hypothesized that netrin‐1 may also act as a ligand for neogenin during neurulation. Here we demonstrate that morpholino knockdown of Xenopus netrin‐1 results in delayed neural fold apposition and neural tube closure. We further show that netrin‐1 functions in the same pathway as neogenin and RGMa during neurulation. However, contrary to the role of neogenin‐RGMa interactions, neogenin‐netrin‐1 interactions are not required for neural fold elevation or adhesion between neuroepithelial cells. Instead, our data suggest that netrin‐1 contributes to the migration of the neural folds towards the midline. We conclude that both neogenin ligands work synergistically to ensure neural tube closure. © 2012 Wiley Periodicals, Inc., 2013